Clinico Pathological Correlation of Chronic Obstructive Pulmonary Disease among Rural Population of North India - Kumar, Adesh; Krishna, Mani; Dayal, Seema (Annals of Clinical Chemistry and Laboratory Medicine, 2016)
BACKGROUND Chronic obstructive pulmonary disease (COPD) is a major cause of chronic morbidity and mortality in rural population. COPD is characterized by chronic airflow limitation and a range of pathological changes in the lung, some significant extra-pulmonary effects, and important co morbidities which may contribute to the severity of the disease in individual patients. METHODS This study was conducted in Department of Pulmonary Medicine and central laboratory from 1st January 2015 to 31st December 2015 in Rural Institute of Medical Science & Research, Saifai, Etawah (U.P.), India on patients who presented with symptoms of COPD. RESULTS The age group of the patient in the study, ranged from 35 to 85 years. The most common age group was 61-70 years (32.99%). Among these patients 92.95% were males and 7.04% were females. Dyspnoea (84.50%) was the common clinical manifestation. Out of 497 patients, 94.96% were smokers and 5.03% were non-smokers. Among these COPD patients 25.15% males and 4.82% females had normal hemoglobin. Similarly, normal total leukocyte count, differential leukocyte count was seen in 56.13% males and 3.82 % females. The gram negative isolates were 63.32% as compared to 36.82% of gram positive. On sputum cytology, bacteria were found in 64.18% and fungus in 35.81%. During sputum culture, Streptococcus (29.97%), was the commonest bacteria isolated followed by Moraxella (25.55%) and Pseudomonas (16.90%). Fungal isolates were Aspergillus (27.96%) and Candida spp. (7.84%). CONCLUSIONS COPD was common in older age group, males, and smokers. Patients predominantly presented with dyspnea and chronic cough. Streptococcus was the most common organism isolated and fungus species were also isolated.